Culture, trauma, and conflict : cultural studies perspectives on war - Carpentier, Nico (Cambridge Scholars Publishing, 2015)
War was pervasive in the 20th century, and the 21st century seems to hold little promise of improvement. It remains one of the world's most destructive forces, which, on a daily basis, touches the lives of millions of people. To increase an understanding of the pervasiveness and destructiveness of the institution of war, all possible frameworks of knowledge must be mobilized. Cultural War Studies has an important role to play in adding to this knowledge, by putting the critical vocabulary of ...